Market opportunities for nutraceuticals from consumer psychology (GEON Journal (Management, Organizations and Business), 2017)
The exhibited work was to assess the market potential for the design, production and distribution of confectionery nutraceutical and bio-fertilizers from agricultural products in the department of the Atlantic. To do this, it was necessary to analyze the expectations and buying habits of potential consumers, potential demand and profile identification lifestyle expectations associated with nutraceutical products and confectionery biotefertilizantes. Using the information analyzed relevant marketing strategy for the promotion and marketing of innovative nutraceutical products confectionery and bio-fertilizers produced in the department of the Atlantic was determined.This research project was funded by COLCIENCIAS and executed by the group of Innovation Research and development enterprise-GIDE. The research approach for this phase of the project was quantitative descriptive, two assessment instruments were applied. The first, a survey of 12 points, developed by the authors to inquire about buying habits and potential demand for nutraceutical products in three product lines (chocolate, bakery). The second questionnaire lifestyle PEPS-I (Pender, 1996) consisting of 48 questions with four answer choices that assesses six dimensions: nutrition, exercise, health responsibility, stress management, interpersonal support and self-actualization. The instruments were applied to seniors 400 the city of Barranquilla.From the analysis, it could be inferred about the characteristics of the participants, trends and common behaviors of potential consumers of the product, especially with regard to consumer preferences, presentation, price, quality, being less important attention and the brand recognition among other variables, as a result the consumer profile is established and defined lines and products marketed by cooperatives.
Keywords: Consumer psychology; food; nutraceitic